2022
DOI: 10.53756/jjkn.v2i1.51
|View full text |Cite
|
Sign up to set email alerts
|

Mengukur Kemampuan Mengiur untuk Jaminan Kesehatan Nasional (JKN) tahun 2021 di Indonesia

Abstract: The purpose of this study is to conduct measurements of the of Indonesians in the National Health Insurance (JKN) in 2020-2021. Indonesia, as of now, implements a national health insurance service since 2014. It is expected that JKN will expand its coverage to achieve universal health coverage (UHC) in Indonesia. BPJS Kesehatan (BPJS-K) was appointed as the administrator of JKN and had experienced deficit until 2019. One of the weaknesses of JKN in revenue collection is the absence of cross subsidy and pegged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 4 publications
0
1
0
Order By: Relevance
“…This phenomenon is because most respondents choose the JKN membership class based on the benefits of the services provided and the number of contributions that must be paid every month. This result aligns with similar research conducted in Bekasi in 2022 (Maulana et al, 2022), which shows that some people have the ability to contribute more to JKN, thus making JKN have a better sustainable financial capacity; however they do not want to pay more because most of the PBPU (Pekerja Bukan Penerima Upah) of the informal sector workers have uncertain wages.…”
Section: Jkn Membership Preferencesupporting
confidence: 89%
See 1 more Smart Citation
“…This phenomenon is because most respondents choose the JKN membership class based on the benefits of the services provided and the number of contributions that must be paid every month. This result aligns with similar research conducted in Bekasi in 2022 (Maulana et al, 2022), which shows that some people have the ability to contribute more to JKN, thus making JKN have a better sustainable financial capacity; however they do not want to pay more because most of the PBPU (Pekerja Bukan Penerima Upah) of the informal sector workers have uncertain wages.…”
Section: Jkn Membership Preferencesupporting
confidence: 89%
“…The higher the increase, the fewer they agreed (Table IV), which is similar to the results of previous research conducted in Bulukerto District (Budiono et al, 2021), which shows that 23 of 28 respondents had an objection to the increase of the JKN membership fee. This result needs to be watched out for because objections to contribution rates will affect compliance with the payment of contributions (Kamila & Rochmah, 2023;Mekarisce et al, 2022), which will then result in a deficit in BPJS Health (Maulana et al, 2022).…”
Section: Wtp For Jkn Membership Feementioning
confidence: 99%
“…Moreover, data published by the Statistics Indonesia (Badan Pusat Statistik - BPS) revealed that between 2014 and 2021, the average monthly household expenditure of urban households increased from IDR 979,000 in 2014 to IDR 1,487,000 in 2021, or by 70%. However, the average monthly household expenditure in rural areas increased by only 52%, from IDR 573,000 in 2014 to IDR 971,000 in 2021 [ 37 ]. With the same level of health care costs, the incidence of CHS would be lower for households in urban areas due to the higher average income.…”
Section: Discussionmentioning
confidence: 99%
“…There are several terms used to describe the meaning of social security, such as social security [36], social insurance, or commonly social welfare [37]. In the Merriam-America Dictionary, it is defined as the principle or practice or program of public provision (as through social insurance or assistance) for the economic security and social welfare of The first dimension is the guaranteed population.…”
Section: National Health Social Securitymentioning
confidence: 99%